Pulmonary hypertension and pulmonary artery dissection - Corrêa,Ricardo de Amorim (2013)
Pulmonary artery dissection is a fatal complication of long-standing pulmonary hypertension, manifesting as acute, stabbing chest pain, progressive dyspnea, cardiogenic shock, or sudden death. Its incidence has been underestimated, and therapeutic options are still scarce. In patients with pulmonary hypertension, new chest pain, acute chest pain, or cardiogenic shock should raise the suspicion of pulmonary artery dissection, which can result in sudden death.